Correlation between microstructure and mechanical properties of Ti(C, N)-xWC-Ni cermets prepared by mechanical activation and subsequent in situ carbothermal reduction. Issue 10 (15th May 2021) - Xu, Xiangyu; Zheng, Yong; Zhang, Jiajie; Ke, Zheng; Wu, Hao; Xue, Chaogang
Abstract: Herein, Ti(C, N)-based cermets prepared via mechanical activation and subsequent in situ carbothermal reduction was studied. The correlation between microstructural and mechanical performance of these cermets was investigated by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. Results indicated that with the increase in tungsten carbide (WC) content, hard particles of ceramic gradually evolved from complete solid solution to partial solid solution with a little quantity of core–rim structure. Mean particle size of the cermet first increased, and then, slightly decreased. In addition, grain shape gradually changed from relatively faceted to nearly round. Initially, with the increase in WC content, the increase in transverse rupture strength (TRS) and slight increase in hardness were related to the strengthening of both solid solution and fine grains. However, with further addition of WC, the decrease in hardness was primarily because of lower hardness of (Ti, W, Mo) (C, N) phase with higher W content. Extremely high toughness of cermets with WC content of 0 and 3 wt% was mainly due to the decrease in interface area compared to traditional cermets, which resulted in significant reduction in interfacial strain between the rim and core. Moreover, toughness improvement of cermets containing 6 to 12 wt% of WC was due to comprehensive effect of superb coherent relationship of black core/grey rim particles, semi-coherent relationship with high-density dislocations of solid-solution particles, and solid-solution strengthening of white core-grey rim particles.